Supply chain performance analysis using discrete system simulation method: A case study in a furniture company - Trenggonowati, Dyah Lintang; Ulfah, Maria; Ridwan, Asep; Bahauddin, Achmad; Ekawati, Ratna; Sonda, Atia; Umyati, Ani; Fachrur, Aditya Rahadian; Yadi, Yayan Harry (Journal Industrial Servicess, 2023)
As time progresses, the evolving industrial world demands that companies devise the best strategies to achieve their desired goals. A well-designed system is expected to increase the profitability of the company itself. CSD is an interior furniture and interior design studio located in the city of Cilegon, Banten. The challenge faced by CSD is the inability to meet order deadlines during periods of high demand. The objective of this study is to assess the level of machine utility within the existing process and provide recommendations to achieve an optimal process. The methodology employed includes system simulation and model development using Promodel software. Additionally, statistical tests, model validation, and ANOVA tests were conducted. Based on the results, it was determined that the level of machine utility at CSD is 17.48% for shaping planning, 30.08% for grinding, 14.88% for assembly, and 29.98% for finishing. The proposed solution, scenario or proposal 2, suggests combining the assembly and finishing workstations, resulting in increased machine utility.